2017
DOI: 10.1111/ijpp.12364
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of care – a randomised control trial investigating the effect of sending the details of patients’ discharge medication to their community pharmacist on discharge from hospital

Abstract: Sending a copy of patients' discharge letters to their community pharmacists could be beneficial in reducing post-discharge prescribing discrepancies and improving patient understanding of the changes made to their medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 8 publications
0
37
1
Order By: Relevance
“…In total, 14 studies reported data concerning the frequency of UMDs [49,50,57,59,60,66,70,74,83,84,88,93,95,98]. Three studies [83,84,93] used an established UMD definition, seven [49,50,59,60,70,74,95] developed their own and four [57,66,88,98] did not report any definition.…”
Section: Unintentional Medication Discrepancy Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 14 studies reported data concerning the frequency of UMDs [49,50,57,59,60,66,70,74,83,84,88,93,95,98]. Three studies [83,84,93] used an established UMD definition, seven [49,50,59,60,70,74,95] developed their own and four [57,66,88,98] did not report any definition.…”
Section: Unintentional Medication Discrepancy Studiesmentioning
confidence: 99%
“…Table 4 summarises outcome rates of the included studies per patient population. [72], three ADR studies [62,64,91], nine ADE studies [24, 54-56, 61, 69, 78, 80, 94] and five UMD studies [59,66,70,88,95]. Seven studies [54,61,62,64,72,78,80] reported severity assessment based on existing rating scales published in the literature.…”
Section: Adverse Drug Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen (44%) had greater levels of involvement that included activities such as home visits, medication therapy management sessions, comprehensive medication reviews, motivational interviewing, identification and resolution of drug therapy problems, and patient education. [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Twenty-three studies were randomized trials, [19][20][21][22][23][26][27][28][29][30][31][32][33][34][36][37][38][39][40][41][42][43][44][54][55][56] with the remaining 13 studies consisting of various nonrandomized designs. 18,24,25,35,[45][46]…”
Section: Resultsmentioning
confidence: 99%
“…A small number of studies have explored how community pharmacists can participate in medication management for patients moving from the hospital to home. Interventions have included contacting community pharmacists to update them on medication changes, [19][20][21] on-site outpatient pharmacists meeting with patients to provide initial fills of new medications and counseling, 22 home visits, 23 and telephone follow-ups. 22,24 Pharmacists working in community settings have positive attitudes about their impact on care transitions but have identified barriers such as limited time and difficulty getting the necessary patient data needed to understand the patient's postdischarge medication orders.…”
mentioning
confidence: 99%